“Becoming Sheep” by Charlotte Grum. A Zoe-Egalitarian Turn in the Artistic Practice - Dworak-Mróz, Magdalena (Sensus Historiae, 2020)
Charlotte Grum is a transdisciplinary Danish artist, consciously undertaking an artistic dialogue with the theoretical foundations of posthumanism. In 2015, as part of the collective exhibition “Descendants”, she made site specific performances entitled “Becoming Sheep.” Five hours a day, five days in each of the five weeks of the campaign, Grum spent her time, connected with a harness to a live sheep, walking along the Danish moors, establishing a close relationship with the animal and the surroundings. Performance chosen as a form of artistic expression emphasized the processual aspect of the project, its openness to external factors, modifications. The starting point for her artistic practice has become the concept of intra-action by Karen Barad, a continuous relationality of action, constituted by interdependent entities, both human and nonhuman, animals and things. In this way, Grum “wanted to explore the discursive and material effects of the interaction of human and nonhuman animals in order to challenge the gender and anthropocentric reading of history...”. On the basis of posthuman research, Rosi Braidotti used the term “zoe-egalitarian turn” to encourage us to establish more just relationships with animals. It was the search for an empathetic pattern of building new human / animal relationships that inspired Charlotte Grum in the “Becoming Sheep” project. In the proposed paper, the theoretical foundations of post-antropocentrism in the writings of Karen Barad, Rosi Braidotti, will be tools for analysing the artistic activity of Charlotte Grum.